The Effectiveness of discovery learning model integrating PhET simulation media to enhance understanding of optical concepts - Nurul Agniya, Nadia; Ismail, Ali; Sari, Lasmita (Insitut Pendidikan Indonesia, 2023)
This study aims to examine the increase in students’ understanding of the optical geometry concept after being given treatment using the discovery learning model assisted by PhET simulation media and to test the effectiveness of this learning model to improve understanding of the optical geometry concepts. The method used in this research is quasi-experimental and uses the research design The Static Group Pretest-Post-test Design. The sampling technique in this study was taken using purposive sampling, namely where the control and experimental classes were selected based on the suitability of the student’s character with the researcher’s goals. Each experimental and control group consisted of 35 participants. The experimental class used the discovery learning model assisted by PhET simulation media and the control class uses the conventional learning model. The instrument in this study was using a multiple-choice test of 20 questions. Based on the test results of the Independent Sample Test, it obtained a significance value (alpha = 0.0001 < 0.05), which means that there is a difference in increasing understanding of the optical geometry concept between classes using the discovery Learning model assisted by PhET simulation media using the learning model conventional.